Multi-dimensional review of Peru. Vol. 1, Initial assessment - Organisation for Economic Co-operation and Development (OECD development pathways, ISSN 2308-734X, 2015)
Summary.
Keywords: taloudellinen kehitys : Peru; talouskasvu : Peru; hyvinvointi : Peru; köyhyys : Peru; kestävä kehitys : Peru; kehitysmaat : Peru